1963
DOI: 10.1126/science.139.3557.833
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Foreign Body: Effect on Pregnancy in the Rat

Abstract: A silk suture placed in the lumen of one uterine horn of rats before mating prevented pregnancy in that horn although normal implantation occurred in the unoperated horn. The suture did not interfere with fertilization or the tubal transport of ova, nor did it induce a decidual reaction; it appeared to prevent pregnancy by causing failure of implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

1964
1964
1984
1984

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 1 publication
0
18
1
Order By: Relevance
“…The animals were ovariectomized and a surgical silk suture was inserted through the anti-mesometrial wall of the right uterine horn according to the procedure of Doyle & Margolis (1963). In another group, the silk suture was inserted in intact animals.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were ovariectomized and a surgical silk suture was inserted through the anti-mesometrial wall of the right uterine horn according to the procedure of Doyle & Margolis (1963). In another group, the silk suture was inserted in intact animals.…”
Section: Animalsmentioning
confidence: 99%
“…Investigations on the mode of action of IUDs have revealed that these devices may be acting by different mechanisms in different species and, since the material from which these devices are made varies, this may also affect their mode of action. In general, it appears that an IUD prevents conception by disturbing the implanta¬ tion processes in some manner in women (Jessen, Lane & Greene, 1963), rats (Doyle & Margolis, 1963), rabbits (Adams & Eckstein, 1965) and cows (Hawk, Conley, Brinsfield & Righter, 1965). There is a lack of information on the biochemical changes produced by IUDs.…”
Section: Introductionmentioning
confidence: 99%
“…Occasional spermatozoa were observed in the glands of the chalaziferous region of the oviduct (Van Drimmelen, 1946) in both treated and control hens. Doyle & Margolis (1963) found that in the rat fertilization was not affected when a loop of surgical thread was placed through the wall of the uterus, but implantation was prevented. Our findings suggest that the presence of a similar foreign body in the shell-gland of the hen for a month or less did not prevent spermatozoa ascending the oviduct after insemination, but survival of sper¬ matozoa in their storage site(s) for long periods was affected adversely.…”
Section: Society For the Study Offertility 273mentioning
confidence: 99%
“…The contraceptive action exerted by a silk suture placed within the rodent uterus has been the subject of a large number of studies since the effect was described by Doyle & Margolis in 1963. At the present time, it is still not clear how such a contraceptive action is brought about, although it seems likely that the presence of a thread induces an intra-uterine environment which is un¬ favourable to the survival of the fertilized egg, and that it also prevents the differentiation of normal decidual cells.…”
Section: Introductionmentioning
confidence: 99%